MICRO, SMALL, AND MEDIUM ENTERPRISES (MSME) CART-MAKING - Hermawansyah, Adi; Norhidayah, Siti; Zamzam, Muhammad; Jelina, Sherly; Saputri, Maulidya Fathimah; Prastistha, Erica Agni; Amelia, Riska; Rifka, Rosmida; Ferry, Christian; Malik, Syahrul; Imelba, Wianda Faza; Chuarajab Ms., Tawakkal (LPPM Univ. Ibn Khaldun Bogor, 2024)
The development of micro, small and medium enterprises (MSME) play a vital role in improving the local economy and expanding economic opportunities for the community. One effective strategy in supporting the growth of MSME is through creating business carts that can function as a mobile platform for selling products or services. This research aims to examine the process of making MSME carts with a focus on design innovation, materials used, and efficient and environmentally friendly production methods. Research methods involve literature analysis, field surveys, and interviews with relevant stakeholders. The research results show that the use of appropriate technology and materials can increase the durability, safety and aesthetics of MSME carts, while the use of efficient production methods can reduce production costs and speed up processing time. The practical implications of this research are to provide practical guidance for MSME in choosing designs, materials and production methods that suit their needs and to encourage the government and related institutions to provide adequate support and facilities for the development of MSMEs through the manufacture of business carts. Thus, this research has the potential to make a significant contribution to increasing the competitiveness of MSME and strengthening the local economy in a sustainable manner.